A coupled phase field/diffusional/mechanical framework for simulation of upper and lower bainitic transformation. (1st May 2019) - Düsing, Martin; Mahnken, Rolf
Abstract: The microstructure bainite in steels consists of three phases, namely bainitic ferrite, austenite and carbide. Two different arrangements of these phases can be observed denoted as upper and lower bainite which develop at different temperatures. For both morphologies the growth starts with a displacive transformation from austenite to bainitic ferrite. The bainitic sheaf has a preferred direction of growth due to eigenstrains which evolve during the transformation. Subsequently a temperature dependent diffusion process starts to redistribute the carbon and carbides precipitate at accumulations of carbon. The goal of this work is to simulate the upper and lower bainite transformation considering eigenstrain effects. To this end, we extend an own previously developed model by mechanical contributions. The related coupling terms of the phase field/diffusional/mechanical model are derived within a thermodynamic framework. Two representative examples illustrate the capability of the extended framework and show the expected transformation of upper and lower bainite.